TALABALARNING O‘ZIGA IShONChINI RIVOJLANTIRIShGA TA’SIR KO‘RSATUVChI IJTIMOIY PSIXOLOGIK OMILLAR TAHLILI - Dawkeeva, A.O. (SCIENCE and SOCIETY, 2025)
This article presents data on the analysis of socio-psychological factors influencing the development of self-confidence in future teachers, the so-called "assessment of a person’s attitude towards themselves" and the preliminary results obtained from the "questionnaire that determines the psychological characteristics of the development of self-confidence in future teachers."